Mineralogical and Maturation Considerations of the Coqueiros Formation (Campos Basin, Brazil): Insights from Multi-Technique Analyses of Source Rocks - Gabriel A. Barberes; Flávia C. Marques; Dalva A. L. Almeida; Linus Pauling F. Peixoto; Lenize F. Maia; Antonio Carlos Sant’Ana; Gustavo F. S. Andrade; Celly M. S. Izumi; Victor Salgado-Campos; Thiago Feital; Luiz Fernando C. de Oliveira; Ana Luiza Albuquerque (Geosciences, 2024)
The Coqueiros Formation, a strategic stratigraphic unit within the Lagoa Feia Group (LFG) in the Campos Basin offshore Brazil, is known for its lacustrine carbonate deposits, which include both organic-rich shales and economically important “coquina” reservoirs. While coquina facies are widely recognized as reservoirs, the source-rock potential of the intercalated shales remains relatively underexplored. This study aims to characterize the mineralogy and thermal maturity of the Coqueiros Formation to assess its potential as a source rock, using a multi-technique approach integrating X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Raman spectroscopy analyses of shale samples from two wells: 3-BP-11-RJS and 6-DEV-18P-RJS. XRD analyses revealed a heterogeneous mineralogy dominated by carbonates (calcite and dolomite) and quartz, with significant contributions from clay minerals and trace minerals such as pyrite and barite. SEM imaging revealed a heterogeneous fabric with grain size, morphology, and porosity variations, reflecting a dynamic lacustrine depositional setting influenced by storm events and fluctuations in terrigenous input. The presence of authigenic minerals, as reported in other studies, such as saddle dolomite, mega-quartz, and various sulfides, provides evidence for hydrothermal alteration, likely related to Late Cretaceous magmatic activity in the Campos Basin. Raman spectroscopy yielded equivalent vitrinite reflectance (Ro%) values consistently exceeding 1.00, ranging from 1.03 to 1.40, indicating that the organic matter in the Coqueiros Formation shales has attained a high thermal maturity level, surpassing the oil window and reaching the condensate wet gas zone. The mineralogical and equivalent maturation data presented herein provide a valuable foundation for future studies, highlighting the complexity and heterogeneity of the Coqueiros Formation and its potential significance as a source rock within the Campos Basin petroleum system.